2007
DOI: 10.1080/00268970701211626
|View full text |Cite
|
Sign up to set email alerts
|

Modelling nucleation and nano-particle structures

Abstract: Molecular modelling methods, including Simulated Annealing/Energy Minimization, Molecular Dynamics and Density Functional Theory are used to probe the nano-structures and aggregation mechanisms involved in the nucleation of two classes of inorganic material: microporous silicas and the II/VI semiconductor, ZnS. Simulations reveal a new structural chemistry for nano-particulate ZnS and provide insight into the pre-nucleation mechanisms of both classes of material. Studies of the silica systems emphasize the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 36 publications
(47 reference statements)
2
15
0
Order By: Relevance
“…40 and 41, which also place these studies into the context of the wider field of computational modeling of nano-clusters. Moreover, although much remains to be done, the calculations establish the viability and value of modeling in studying the early stages of zeolite synthesis.…”
Section: Review Articlementioning
confidence: 95%
See 2 more Smart Citations
“…40 and 41, which also place these studies into the context of the wider field of computational modeling of nano-clusters. Moreover, although much remains to be done, the calculations establish the viability and value of modeling in studying the early stages of zeolite synthesis.…”
Section: Review Articlementioning
confidence: 95%
“…35,36 Such an approach was employed by Mora-Fonz et al, [37][38][39][40] where the basis was still DFT calculations, but explicit water was included and the whole silicate-water complex was embedded in the continuum-like representation of solvation available in the ''COSMO'' approach. Upon water removal, a negatively charged dimer is formed.…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…They observed that at time scales shorter than 0.5 ns fourmembered rings will be most common, while at time scales longer than 1 ns five-membered rings will dominate. Very recently, Mora-Fonz et al have shown the importance of solvent and pH to control specific oligomerization and cyclization processes in the nucleation of microporous silicas [56,57]. Wu and Deem have shown that the nucleation barrier of silica without templates at high pH (*12) lies around 50 T atoms [58].…”
Section: Introductionmentioning
confidence: 97%
“…Polymorph selection is important for controlling structure during the synthesis of materials from pharmaceuticals [27][28][29][30] to zeolites 31,32 and biominerals. Polymorph selection is important for controlling structure during the synthesis of materials from pharmaceuticals [27][28][29][30] to zeolites 31,32 and biominerals.…”
Section: Introductionmentioning
confidence: 99%